The level of organizational loyalty of employees in sport management - صواش عيسى, (sports creativity, 2025)
The research aimed to know the level of organizational loyalty in a sample of the employees of the sports management represented by the Directorate of Youth and Sports of the state of M’sila, the researcher relied on the descriptive approach in the survey method, and the research tool was represented in the organizational loyalty scale designed by Allen and Mayer in 1990, the sample size was 22 employees in the Directorate of Youth and Sports of the State of M’sila during the month of March 2019, the researcher concluded that the employees of this institution have an average level of organizational loyalty, the study recommended the need to observe the system of material and moral incentives, And activating the communication system and participation of decision-making personnel to increase the organizational loyalty of